Adverse local tissue reactions in arthroplasty: opportunities and challenges for a common terminology across scientific, clinical and regulatory fields - Anastasia Rakow; Frank Schulze; Janosch Schoon; Ivan De Martino; Giorgio Perino (EFORT Open Reviews)
Clinicians, scientists and regulators do not use a common set of definitions and terminology to classify and code periprosthetic tissue reactions to wear debris of arthroplasty implants and a limited granularity is present to allow early identification of associated adverse events. Adverse local tissue reactions (ALTRs) is an umbrella term, which has been used in particular for periprosthetic tissue reactions to metal wear debris. In this review, it has been extended to all implant materials and adverse reaction to metallic debris as a subset of ALTR caused by or associated with metallic particulate debris. The high variability in the terminology of ALTRs used by national arthroplasty registries, various coding systems and clinicians impedes their accurate reporting and interpretation, crucial for evaluating the reasons for implant failure and revision arthroplasty. Histopathological examination of periprosthetic soft tissue and bone uses standardized criteria for the diagnoses of reactions to wear particles, significantly contributing to their understanding and refining their interdisciplinary terminology.This review critically analyzes the current gap in coding ALTRs due to arthroplasty implants’ wear in national registries and classification systems of adverse events and the use of key terms. A comprehensive unified lexicon and classification system grounded on evidence-based histopathological analyses is proposed, implementing the following findings. (a) Pseudotumor is a descriptive term for ALTR, which cannot be used for codification. (b) Metallosis is a term lacking quantitative and qualitative determination and thus not a codifiable term for ALTR. (c) Aseptic lymphocyte dominant vasculitis-associated lesion (ALVAL) should not be used due to absence of histological findings diagnostic of vasculitis. (d) Metal delayed hypersensitivity and metal allergy should be codified as separate categories of adverse events. (e) ALTR is to be classified in due consideration of definition of predominant lymphocytic or predominant macrophage infiltrate. (f) Granulomatous reaction should be reserved to sarcoid-like, immune granulomas separated from the macrophage infiltrate with/without foreign body giant cell reaction. (g) Macrophage infiltrate containing particulate wear debris with or without lymphocytic component associated with macrophage induced osteolysis/aseptic loosening should be considered as a type of ALTR.